Patellar Tendinopathy: Diagnosis and Treatment. Issue 12 (December 2016) - Figueroa, David; Figueroa, Francisco; Calvo, Rafael
Abstract : Patellar tendinopathy is a common cause of pain in athletes' knees. Historically, it has been related to jumping sports, such as volleyball and basketball. Repetitive jumping generates a considerable load of energy in the extensor mechanism, leading to symptoms. The main pathophysiologic phenomenon in patellar tendinopathy is tendinosis, which is a degenerative disorder rather than an inflammatory disorder; therefore, the other popular term for this disease, tendinitis, is not appropriate. The nonsurgical treatment of patellar tendinopathy is focused on eccentric exercises and often has good results. Other experimental options, with variable levels of evidence, are available for recalcitrant cases. Surgical treatment is indicated for cases that are refractory to nonsurgical treatment. Open or arthroscopic surgery can be performed; the two methods are comparable, but arthroscopic surgery results in a faster recovery time.